Evaluation of a digital health platform for preventing stroke in the Australian community: Study protocol for a randomized controlled trial – Love Your Brain - Monique F. Kilkenny; Dominique A. Cadilhac; Amanda G. Thrift; Mark R. Nelson; Janet Bray; Jan Cameron; Timothy Kleinig; Muideen T. Olaiya; Lisa Murphy; Tara Purvis; Rosanne Freak-Poli; Catherine Burns; et al. (PLoS ONE, 2025)
Rationale One in four people will have a stroke in their lifetime. Over 80% of strokes are preventable through the management of modifiable risk factors. There is a growing demand from the community for information about how to prevent stroke. The Love Your Brain digital platform comprises an online course (Massive Online Open Course) and text messages to improve stroke knowledge and motivate behaviour change for stroke prevention. Aims To determine the effect of the digital platform vs a control on attendance at a medical practitioner for cardiovascular risk assessment or management, from either a general practitioner or specialist. Methods and design Love Your Brain is a Phase III, prospective, single-blinded three-arm randomized controlled trial. Eligible participants are community-dwelling residents of Australia aged ≥45 years, who communicate in English language, can access internet and a smartphone, and do not have a self-reported history of stroke or major cardiovascular event. Participants are randomised to either receive the online course, text messages, or general information about stroke risk factors via email (control). Online surveys will be conducted at baseline and 12 weeks. Outcomes will be assessed based on intention-to-treat analysis. Self-reported medical visits will be validated using data linkage. Process and economic evaluations will be conducted in parallel to the trial. An independent statistician blinded to group will analyse the data. Study outcomes and sample size The primary outcome is a visit to a medical practitioner for cardiovascular risk assessment or management within 12-weeks of randomization. Secondary outcomes include: (1) knowledge of stroke signs and risk factors; (2) healthy or risk-modifying behaviours; (3) adherence to medications; (4) process evaluation including intervention delivery/implementation and satisfaction; (5) economic evaluation including health care resource use and cost; and (6) adverse events. Assuming 80% power (two-sided α = 0.05) and 40% prevalence in the control group, 894 participants (298 for each of three groups) will be required to detect a 30% relative increase in medical practitioner attendance for cardiovascular risk assessment or management from either a general practitioner or specialist in the intervention groups. Discussion This study will provide evidence for the efficacy of a low-cost digital health intervention (online course or text messages) to reduce the risk of stroke in the community. Trial registration ACTRN12625000124437